Overview of Teachers' Mental Challenges, Competences, and Readiness to the Transition to Distance Learning in the UAE - Moussa N.M; El Khalil N.S (Moscow State University of Psychology and Education, 2022)
The Coronavirus pandemic outbreak has changed numerous life activities. The education sector is one of many sectors that have been heavily impacted by the pandemic. Necessitating a transition to virtual distance learning challenged educators' adaptation towards using online platforms for teaching and assessment. This study examines (1) teachers' perception of their competencies and readiness to the online mode of learning in the United Arab Emirates (UAE), (2) teachers' mental states during the Coronavirus pandemic, and (3) the relationship between teachers' perception of competencies and their mental states. A Teachers' Competency Measurement Scale (TCMS) was developed to achieve the purpose of this research study. Data was collected quantitatively from 232 teachers who have teaching obligations for grades K-12 in the UAE. The findings showed that most of the teachers in the UAE feel competent and ready for the transition to the online learning environment. The Correlation Coefficient analysis revealed that there is no relationship between teachers' perception of competencies and their mental states. Furthermore, the Coronavirus affected teachers negatively.